Design and implementation of a high-fidelity AC metering network - Jiang, Xiaofan; Dawson-Haggerty, Stephen; Dutta, Prabal; Culler, David (2009 International Conference on Information Processing in Sensor Networks, 2009)
We present the architecture, design, and preliminary evaluation of ACme, a wireless sensor and actuator network for monitoring AC energy usage and controlling AC devices in a large and diverse building environment. The ACme system consists of three tiers: the ACme node which provides a metering and control interface to a single outlet, a network fabric which allows this interface to be exported to arbitrary IP endpoints, and application software that uses this networked interface to provide various power-centric applications. The ACme node integrates an Epic core module with a dedicated energy metering IC to provide real, reactive, and apparent power measurements, with optional control of an attached load. The network comprises a complete IPv6/6LoWPAN stack on every node and an edge router that connects to other IP networks. The application tier receives and stores readings in a database and uses a web server for visualization. Nodes automatically join the IPv6 subnet after being plugged in, and begin interactions with the application layer. We evaluate our system in a preliminary green building deployment with 49 nodes spread over several floors of a Computer Science Building and present energy consumption data from this preliminary deployment.